Intricacies in characterizing positivity in pooled sample testing for SARS‐CoV‐2. Issue 5 (23rd February 2021) - Mohanty, Srujana; Ravindra, Akshatha; Gupta, Kavita; Hallur, Vinaykumar; Behera, Bijayini; Mahaptra, Ashoka; Saha, Swarnatrisha; Ranjan, Jai; Payal, Poesy; Mohanty, Monalisa; Rath, Sutapa; Mishra, Baijayantimala
Abstract: The unprecedented demand for testing for the ongoing coronavirus disease 2019 (COVID‐19) pandemic caused by severe acute respiratory syndrome coronavirus 2 has led to an acute shortage and limited availability of test reagents for which pooling of samples has been recommended in areas with low prevalence. Considering the possibility of dilution factor in pool testing, an attempt was made to find out possibility of any true positive samples in pools with late amplification. The study was conducted on samples received from various collection centers in different districts of Odisha as well as from patients attending the screening clinic or admitted in COVID ward of the hospital. Nasal/nasopharyngeal/throat swabs received in viral transport media in cold chain were subjected to Real‐time polymerase chain reaction (RT‐PCR) testing in a Biosafety Laboratory level‐2 by including uniform volume of four units (samples) per pool. All confirmed and probable positive pools in screening assay were de‐convoluted and individual samples tested for confirmatory assay. Inclusion of an additional criteria of probable positive pool ( C t value >35 with non‐sigmoid amplification curve or showing a line of amplification towards the end of the cycle) yielded 39 (15.5%) more true positive samples out of a total of 251 positive samples that would otherwise have been missed if only the classical criteria of positive ( C t within 35 with proper sigmoid curve) had been considered. The study highlights the importance of considering any indication of late amplification in the RT‐PCR test to label a pool as positive to avoid missing any true positive sample in the pool.